Dinâmica da alimentação de peixes piscívoros da Represa de Três Marias (MG) - Peret, André Moldenhauer (Universidade Federal de São Carlos, 2004)
The fish feeding study is a valuable tool on understanding the interactions between populations in a community. The Três Marias reservoir, on the high region of the São Francisco River (MG), is a typically oligotrophic environment with a high density of piscivorous fishes (about 20% of the total icthyomass). To support this trophic guild on environments like this, it is expected a high aloctone matter input. In such environment, in the high waters period, the marginal area is flooded, providing food to the fodder species, which support the piscívorous communities. During this period, the contribution of terrestrial insects is fundamental to support many fish species. It was analyzed the stomach content of five piscívorous species (Serrasalmus brandti, Pygocentrus piraya, Pachyurus squamipennis, Acestrorhynchus britskii and Acestrorhynchus lacustris) in four distinct periods of the year and four stations in the reservoir. The food items importance was estimated using the feeding index. S brandti was the only piscívorous species responsible for the incorporation of aloctone matter, basically terrestrial insects. The other species showed a high niche overlap during the high waters period (higher food providing), when they feed basically upon Anchoviella vaillanti, and had a wide niche overlap reduction in the low waters period, what characterizes a niche displacement. It was detected, on the station that receives domestic waste, a reduction on the niche overlap, an indication of a change on the food offer, as a consequence of the environmental pollution or even of the enrichment by the additional organic matter input.
Keywords: Comunidade de peixes; Peixe alimentação; Três Marias, Reservatório de (MG); Ecologia trófica; Piscívoros; CIENCIAS BIOLOGICAS::ECOLOGIA